Gold-catalyzed regiospecific C-H annulation of o-ethynylbiaryls with anthranils: π-extension by ring-expansion en route to N-doped PAHs - Zeng, Zhongyi; Jin, Hongming; Sekine, Kohei; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2018)
We describe a novel, short, and flexible approach to diverse N-doped polycyclic aromatic hydrocarbons (PAHs) through gold-catalyzed π-extension of anthranils with o-ethynylbiaryls as reagents. This strategy uses easily accessible starting materials, is simple due to high step and atom economy, and shows good functional-group compatibility as well as scale-up potential. Mechanistically, the tandem reaction is proposed to involve a nucleophilic addition/ring opening/regiospecific C−H annulation/protodeauration sequence terminated by a Friedel-Crafts-type cyclization. Photophysical studies of the products indicated violet-blue fluorescence emission with quantum yields up to 0.45.
Gesehen am 27.08.2018